2012
DOI: 10.1111/acer.12018
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of α5 Subunit‐Containing GABAA Receptors Alters Alcohol Drinking by Rhesus Monkeys

Abstract: Background Alcohol’s ability to potentiate the activity of γ-aminobutyric acid (GABA) at GABAA receptors has been implicated as a key mechanism underlying the behavioral effects of alcohol. The complex molecular biology of these receptors raises the possibility that particular receptor subtypes may play unique roles in alcohol’s abuse-related effects and that subtype-selective ligands with therapeutic specificity against alcohol might be developed. This study evaluated the capacity of α5GABAA receptor ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
4
27
1
Order By: Relevance
“…One study in nonhuman primates also reported reductions in alcohol drinking following 3-PBC administration, but at higher doses (18 mg/kg) than the doses used in the present study (Kaminski et al, 2012). We chose not to test higher doses due to the emergence of behavioral effects on the observation measures, which indicated the doses were behaviorally active and possibly anxiogenic (Major et al, 2009, Ruedi-Bettschen et al, 2013), but likely not sedative. This study also reported a significant reduction in number of alcohol drinks in the initial 20 minutes of each daily session, corroborating our observation of increased latency to sipper extension (3-PBC: 9 vs 86 sec; βCCT: 4 vs 187 sec).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One study in nonhuman primates also reported reductions in alcohol drinking following 3-PBC administration, but at higher doses (18 mg/kg) than the doses used in the present study (Kaminski et al, 2012). We chose not to test higher doses due to the emergence of behavioral effects on the observation measures, which indicated the doses were behaviorally active and possibly anxiogenic (Major et al, 2009, Ruedi-Bettschen et al, 2013), but likely not sedative. This study also reported a significant reduction in number of alcohol drinks in the initial 20 minutes of each daily session, corroborating our observation of increased latency to sipper extension (3-PBC: 9 vs 86 sec; βCCT: 4 vs 187 sec).…”
Section: Discussionmentioning
confidence: 99%
“…Although nonselective negative modulation (i.e., inverse agonism) of the GABA A receptor was able to alter drinking behavior, these drugs are often hampered by the emergence of side effects. Notably, inverse agonist modulation at the α5GABA A receptor has been shown to selectively reduce alcohol drinking in the absence of severe side effects while a neutral α5GABA A -selective antagonism did not (Ruedi-Bettschen et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations